Effect of distance between the laser spot and the cavity center on spatially confined laser-induced copper plasma - Junwei Jia; Hongbo Fu; Huadong Wang; Zhibo Ni; Fengzhong Dong (AIP Advances, 2019)
We investigated the effect of distance between the laser spot and the cavity center on spatially confined laser-induced copper plasma in air. Spatial cylindrical cavities with various diameters (2mm, 3mm, 4mm and 5mm) and heights (2mm, 4mm, 6mm and 8mm) were used to confine the plasma, and different enhancements were observed when the laser spot at different locations in the same cavity. The maximum enhancement factor for the spectral intensity of Cu atomic line to be around 9 was measured at a time delay of 2.5μs when the distance was 0mm. The plasma temperature was calculated by the Boltzmann plot method, including five Cu atomic lines (324.75nm, 327.40nm, 510.55nm, 515.32nm and 521.82nm). The enhancement of the plasma temperature had a similar trend with the spectral intensity and also showed a strong dependence on the distance. The results demonstrated that the enhancement effect at the center of the cavity was the most significant for the uniform and balanced compression of the reflected shock waves in all directions.